(untitled) (Revista de Estudos da Linguagem, 2019)
Abstract: We present results of a comparative study of beliefs about (i) the pronominal forms a gente (“we”) and tu (“you”) and (ii) the social evaluation of nonstandard verbal agreement with these two pronouns by a group of students from the Federal University of Sergipe (Itabaiana-SE). We discuss the methodological advances in the use of the Iramuteq software, through a multidimensional analysis of beliefs and linguistic attitudes. A survey was designed to measure the attitudes towards the following grammatical patterns: i) a gente (“we”); ii) tu (“you”); iii) a gente vivemos (“we 1PL live 1PL”); and iv) tu vai (“you 2SG go 3SG”). The results reveal that the students’ perception of grammatical patterns is based on dimensions of standardization and vitality; they attribute two types of social values to the linguistic forms: cultural (common, habitual, strange, normal) and normative (correct, wrong). The form a gente vivemos (“we live-1PP”) seems to be the only one to which stigma is attached in the community. The results also reveal that the students link these forms to notions of social adequacy both to the interactional context and to the speech community. The analysis with Iramuteq represents a methodological advance for perception studies, by enabling comparability between the vocabulary used by the students and the linguistic forms under evaluation, and providing an objective, reliable statistical analysis. Keywords: grammatical patterns; variation; linguistic attitudes. Resumo: Apresentamos os resultados de um estudo comparativo entre crenças relativas às formas pronominais a gente e tu e a avaliação social da concordância não padrão com tais formas por um grupo de universitários da Universidade Federal de Sergipe. A partir de uma análise multidimensional das crenças por meio do Iramuteq, objetivamos discutir as vantagens metodológicas do uso desse software para estudos de atitudes linguísticas. Um questionário foi desenvolvido para mensurar as atitudes acerca dos seguintes padrões gramaticais: i) a gente; ii) tu; iii) a gente vivemos; e iv) tu vai. Os resultados evidenciam que a percepção dos universitários em relação aos padrões gramaticais considerados baseia-se nas dimensões de padronização e vitalidade, atribuindo às formas linguísticas dois tipos de valores sociais: cultural (comum, costume, estranho, normal) e normativo (correto, errado). Dentre as formas linguísticas avaliadas, apenas a gente vivemos parece carregar estigma na comunidade, com avaliação negativa. Os resultados mostram também que os universitários atrelam o uso dos padrões gramaticais avaliados à noção de normas sociais de adequação ao contexto interacional e à comunidade de fala. A análise com o Iramuteq representa um ganho metodológico para os estudos de percepção, pois, além de permitir a comparabilidade entre o vocabulário utilizado pelos participantes e as formas linguísticas sob avaliação, oferece uma análise estatisticamente sólida, confiável e objetiva. Palavras-chave: padrões gramaticais; variação; atitudes linguísticas.